Implementasi Fasilitas Intelligent Transportation System (ITS) Di Kota Palangka Raya - Devia Devia; Prihanika Prihanika (Media Ilmiah Teknik Sipil, 2020)
The movement of people and goods is increasing in line with economic growth in society. This causes the potential for increased transportation activities in the City of Palangka Raya so it needs efforts to improve adequate transportation facilities and infrastructure. The application of technology-based Intelligent Transportation System (ITS) in Palangka Raya City is needed so that the management of the transportation system becomes more effective and efficient. This paper provides an overview of the application of ITS facilities and types in Palangka Raya City and provides recommendations for the use of new ITS facilities or optimizing existing technology so that ITS facilities can be utilized by stakeholders in traffic management and transportation systems in Palangka Raya City. Based on observations of the application of ITS in the City of Palangka Raya is applied to improve the performance of intersections and road services. The type of ITS facility is the Area Traffic Control System (ATCS), which is a vehicle traffic control system at the signal intersection to increase travel speed and travel time so that delays in travel can be minimized. It is also expected that the implementation of ITS in Palangkaraya City can also optimize the performance of public transport and traffic safety as well as the collaboration between stakeholders so that the improvement of the integrated transportation system can be well integrated.